2018
DOI: 10.5005/jp-journals-10015-1586
|View full text |Cite
|
Sign up to set email alerts
|

Level of Interleukin-17 in Gingival Crevicular Fluid of Patients with Chronic Periodontitis

Abstract: Aim: Interleukin-17 (IL-17) is a proinflammatory cytokine that plays an important role in inflammation and tissue destruction in periodontal disease. This study aimed to assess the level of IL-17 in gingival crevicular fluid (GCF) of patients with chronic periodontitis (CP) and healthy controls. Materials and methods:This case-control study was performed on 30 patients with CP (53% males, 47% females, mean age of 37.2 ± 5.95 years) and 30 healthy controls (53% males, 47% females, mean age of 30.63 ± 5.22 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The oldest study was from 2005 [ 39 ], and the most recent from 2022 [ 28 ]. Five (41.6%) studies were conducted in India [ 28 30 , 35 , 36 ], two (16.6%) studies in Iran [ 31 , 32 ], and other studies (8.3%) in Saudi Arabia [ 33 ], Japan [ 34 ], Egypt [ 37 ], Turkey [ 38 ], and Chile [ 39 ]. In addition, the title and journals of publication are shown (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oldest study was from 2005 [ 39 ], and the most recent from 2022 [ 28 ]. Five (41.6%) studies were conducted in India [ 28 30 , 35 , 36 ], two (16.6%) studies in Iran [ 31 , 32 ], and other studies (8.3%) in Saudi Arabia [ 33 ], Japan [ 34 ], Egypt [ 37 ], Turkey [ 38 ], and Chile [ 39 ]. In addition, the title and journals of publication are shown (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine (75%) studies collected GCF samples with absorbent paper strips [ 30 35 , 37 – 39 ] and 3 (25%) studies reported GCF collection using volumetric microcapillary pipettes [ 28 , 29 , 36 ]. Among the 12 included studies, 4 (33.3%) used ELISA kits without brand specification [ 30 , 32 – 34 ], two (16.6%) used R&D Systems ELISA kit [ 36 , 39 ], two others (16.6%) used BioSource ELISA kit [ 37 , 38 ], others (8.3%) used RayBiotech [ 28 ], Diaclone [ 29 ], Bender Med Systems [ 31 ] and eBioscience [ 35 ]. Most of the studies (75%) analyzed cytokine IL-17 levels individually [ 28 30 , 32 , 34 , 36 – 39 ], whereas, 2 others (17%) analyzed IL-23 levels [ 33 , 35 ] and only one (8%) analyzed the IL-23/IL-17 axis together [ 31 ] (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…As regards the PI of group B, the difference between T0 and T4 is statistically significant for p <0.05, with t = -33. 16.…”
Section: A Plaque Index Analysis (Pi)mentioning
confidence: 99%
“…The latter act selectively against specific bacterial strains or species and appear capable of eliminating or interfering with the growth of other bacteria genetically "close" to the inhibiting bacterium. Furthermore, unlike viruses, are considered safe by the Food and Drug Administration for administration in humans and have therefore gained popularity in research in the field of probiotics [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation